HCFC‐22 emissions at global and regional scales between 1995 and 2010: Trends and variability. Issue 13 (8th July 2013) - Fortems‒Cheiney, A.; Chevallier, F.; Saunois, M.; Pison, I.; Bousquet, P.; Cressot, C.; Wang, H. J.; Yokouchi, Y.; Artuso, F.
Abstract : [1] HCFC‒22 (CHClF2, chlorodifluoromethane) is an ozone‒depleting substance, the consumption of which is controlled under the Montreal Protocol. Within a Bayesian inversion framework, we use measurements of HCFC‒22 atmospheric concentrations to constrain estimates of HCFC‒22 emissions, at the grid point 3.75°×2.5° and 8 day resolution, from January 1995 to December 2010. Starting from a new gridded bottom‒up inventory which is then optimized, our method shows continuously rising global emissions, from 182±11 Gg in 1995 to the maximum of 410±9 Gg in 2009. This is mainly due to an increase of emissions in developing regions, particularly in Eastern Asia, and occurs despite the current phase‒out in developed countries. The high temporal resolution of our inversion (8 day) allows to reveal some of the emission seasonality, the global posterior sources ranging from 25 Gg/month in November to 42 Gg/month in July, for example, in 2010. Key Points: inversion of HCFC‐22 emissions for the long period 1995 to 2010 reduction of the uncertainties associated with HCFC‐22 emissions revelation of HCFC‐22 emissions seasonality